Formulasi Kaidah Fiqhiyah Tentang Kesulitan, Hukum Asal Ibadah dan Peran Niat dalam Akad Serta Implementasinya - Fathonah Kasuwi Daud (Al Hikmah: Jurnal Studi Keislaman, 2021)
This article discusses the formulation of fiqhiyyah rules regarding difficulties (الميسور لايسقط بالمعسور), the law of origin of worship (الأصل في العبادات الخطر) and the role of intention in the contract (هل العبرة في العقود بصيغ أو بمعـان؟)) and its implementation. Fiqhiyyah rules have been formed in the apostolic era up to the 3rd century AH. However, the new fiqhiyyah rules were recorded in the 4th century AH. This writing method uses literature studies, finding that الميسور لايسقط بالمعسور is a furuiyyah rule of the rule of “المشقة تجلب التيسير” will bring out the convenience. The results of the discussion of this paper found that the first kaidah fiqhiyyah, Islam is an easy religion. Allah gives assignments to some one according to his ability. On the other hand, the law of origin of worship is prohibited unless there is a argument which instructs it to be carried out. However, this only applies to the types of mahḍah worship, so that for ghair mahḍah and ghair muyyan there are no restrictions, such as reading doa, salawat, dzikr, sadaqah and others that can be carried out anytime and anywhere. Meanwhile, the third principle shows that matters of intention in Islam are very important. All matters in worship are assessed for their intentions. Wrong intentions can damage a person's deeds. Keyword: formulation of fiqhiyyah, difficulties, origin of worship, intention in the contract